The Feasibility And Financial Analysis Of Broiler Chicken Farming At Pt Semesta Mitra Sejahtera (A Case Study at Ir. John Isman's Farm, Pelempang Village, Kelekar District, Muara Enim Regency, South Sumatra Province) - Pakpahan, Elizabeth Octa; ., Yulius (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2024)
Broiler chicken farming, a widely embraced agribusiness venture, was recognized for its substantial business value within the community. The research aimed to achieve the following objectives: (1) Evaluate the total expenses incurred by the farmer and establish the feasibility and financial viability of Ir John Isman's broiler chicken farm; (2) Compute the payback period for the investment costs borne by the farmer; (3) Assess the sensitivity of the broiler chicken farm's feasibility in the face of reduced production and chicken prices. Conducted at Ir John Isman's Broiler Chicken Farm in Pelempang Village, Kelekar District, Muara Enim Regency, South Sumatra Province, the research employed a case study method. Primary data was gathered through direct interviews, supplemented by secondary data from literature and other relevant sources. The research findings were as follows: (1) Ir John Isman's Broiler Chicken Farm met comprehensive criteria in feasibility and financial analysis, with an NPV of Rp 11.361.868.688, Net B/C of 2,98, IRR of 32,66%, and a Payback Period of 3,8 years or equivalent to 19 production periods; (2) Sensitivity analysis revealed that Ir John Isman's Broiler Chicken Farm was highly responsive to reduced production and selling prices. Calculations demonstrated that an 9% decrease rendered the farm non-compliant with the criteria for feasibility and financial viability. Keywords: broiler chicken farm and feasibility analysis